In Situ Endothelialization of Free‐Form 3D Network of Interconnected Tubular Channels via Interfacial Coacervation by Aqueous‐in‐Aqueous Embedded Bioprinting. Issue 7 (18th December 2022) - Zhang, Shanshan; Qi, Cheng; Zhang, Wei; Zhou, Hui; Wu, Nihuan; Yang, Ming; Meng, Si; Liu, Zhou; Kong, Tiantian
Abstract: The challenge of bioprinting vascularized tissues is structure retention and in situ endothelialization. The issue is addressed by adopting an aqueous‐in‐aqueous 3D embedded bioprinting strategy, in which the interfacial coacervation of the cyto‐mimic aqueous two‐phase systems (ATPS) are employed for maintaining the suspending liquid architectures, and serving as filamentous scaffolds for cell attachment and growth. By incorporating endothelial cells in the ink phase of ATPS, tubular lumens enclosed by coacervated complexes of polylysine (PLL) and oxidized bacteria celluloses (oxBC) can be cellularized with a confluent endothelial layer, without any help of adhesive peptides. By applying PLL/oxBC ATPS for embedded bioprinting, free‐form 3D vascular networks with in situ endothelialization of interconnected tubular lumens are achieved. This simple approach is a one‐step process without any sacrificed templates and post‐treatments. The resultant functional vessel networks with arbitrary complexity are suspended in liquid medium and can be conveniently handled, opening new routes for the in vitro production of thick vascularized tissues for pathological research, regeneration therapy and animal‐free drug development. Abstract : Endothelialized liquid‐in‐liquid architectures are presented by a three‐dimensional (3D) embedded bioprinting strategy. The interfacial coacervation of aqueous two‐phase systems (ATPS) is exploited for maintaining liquid architectures and serving as filamentous scaffolds for cell growth. The free‐form 3D networks of interconnected endothelium lumens suspended in liquids can be significant for generating functional tissues.